Metal Transfer Behavior and Molten Pool Dynamics in Cold Metal Transfer Pulse Advanced Additive Manufacturing of 7075 Aluminum Alloy - Yili Wang; Dongbin Zhang; Chen Zhang (Micromachines)
Wire arc additive manufacturing (WAAM) with a special arc mode of cold metal transfer pulse advanced (CMT-PADV) is an ideal additive manufacturing process for fabricating aerospace components, primarily high-strength aluminum alloys, offering advantages such as high deposition rates and low cost. However, the numerical simulation of the CMT-PADV WAAM process has not been researched until now. In this study, we first developed a three-dimensional fluid dynamics model for the CMT-PADV WAAM of 7075 aluminum alloy, aiming at analyzing the droplet transition and molten pool flow. The results indicate that, under the CMT-PADV mode, droplet transition follows a mixed transition mode, combining short-circuiting and spray transition. The Direct Current Electrode Positive period of the arc accelerates droplet spray transition, significantly increasing molten pool flow. In contrast, the Direct Current Electrode Negative period of the arc predominantly features droplet short-circuiting transition with low heat input and a weak impact on the molten pool. The periodic switching of the current polarity of CMT-PADV mode results in periodic variations in molten pool size and volume, reducing heat input while maintaining high deposition quality. The revelation of this mechanism provides process-based guidance for low-defect, high-performance manufacturing of critical components.